Leaf nutrient traits exhibit greater environmental plasticity compared to resource utilization traits along an elevational gradient - Zhang, Xing; Duan, Jie; Ji, Yuhui; Liu, Weiguo; Gao, Jie (Frontiers in Plant Science, 2024)
Studying key leaf functional traits is crucial for understanding plant resource utilization strategies and growth. To explore the patterns and driving factors of key leaf functional traits in forests along elevational gradients under global change, we collected survey data from 697 forests across China from 2008 to 2020. This study examined the elevational patterns of Specific Leaf Area (SLA, m²/kg), Leaf Dry Matter Content (LDMC, g/g), Leaf Nitrogen (LN, mg/g), and Leaf Phosphorus (LP, mg/g), and their responses to climate, soil nutrients, and stand factors. The results showed distinct differences in these key leaf traits at different elevational gradients.Generally, as elevation increased, SLA decreased, while LDMC significantly increased (P < 0.001), and LN first increase and then decreased (P < 0.001). The direct influence of elevation on the spatial variation of key leaf traits was greater than its indirect effects (through environmental and stand factors). The elevational patterns of leaf traits related to resource utilization strategies (SLA and LDMC) were mainly influenced by climate (temperature and precipitation) and soil nutrient factors, showing opposite trends in response to environmental changes. The patterns of leaf nutrient traits (LN and LP) along elevational gradients were primarily influenced by climatic factors, with LN exhibiting greater environmental plasticity. Compared to other stand factors, forest age predominantly influenced the spatial variation of key leaf traits, especially SLA. These findings have significant theoretical implications for revealing how plants adapt to global change.